PENGARUH LINGKUNGAN SOSIAL DAN PERSEPSI TENTANG PENDIDIKAN TERHADAP MINAT MELANJUTKAN KE PERGURUAN TINGGI (Studi Pada Siswa Jenjang Pendidikan Menengah yang Bertempat Tinggal Di Desa Sungai Loban Kecamatan Sungai Loban Kabupaten Tanah Bumbu) - Erwin Setiadi (Universitas Lambung Mangkurat, 2015)
Perceptions of education is a cognitive process that is experienced by everyone in understanding information about their environment through sight, hearing, appreciation, feeling, and smell. This study aimed to analyze the low level of education of Sungai Loban villagers. This study used survey method. The study population was all residents of the village of Sungai Loban aged between 16-19 years. Samples of the present study used a non-probability sampling, with the samples of 128 people. The data analysis used descriptive test, test requirement analysis and hypothesis testing using analysis of product moment. This study used a questionnaire as a data collection instrument.The results of this study found that (1) the social environment had a positive influence on the interest to go to college which was proved with r2 value, amounted to 0.0992 or 9.92%, (2) perception of education had a positive influence on the interest to continue to college which was evidenced by the high r2 value, amounted to 0.4173 or 41.73%, (3) the influence of the social environment and perceptions of education to interests of going to college (studies on secondary education students who resided in the village of Sungai Loban Tanah Bumbu regency), simultaneously by 44.3% and the remaining 55.7% was influenced by other factors, but not examined in this study. Students as the next generation should have high education in order to participate in economic development and other fields. The low enrollment rate occured because there were several influencing factors, such as: transportation and other economic factors and personal awareness.Keywords: Social environment, Perceptions about Education, Interests, College.